AN OVERVIEW ON THE CONSERVATION STATUS OF MERSAWA (Anisoptera costata Korth.) IN JAVA - Titi Kalima; Titiek Setyawati (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2007)
Anisoptera costata Korth., which has a commercial name of mersawa grows and proliferates naturally, often gregarious, in semi-evergreen dipterocarp forest and evergreen forest in areas with seasonal climate and rare but widespread in lowland everwet forest from sea level up to 700 m in continental S.E. Asia, Malay Peninsula, Borneo, Sumatra, and Java (Ashton, 1982). In Java, it has been recorded to occur only in Banten (Backer & Bakhuizen van den Brink,1963) and in Leuweung Sancang Nature Reserve (LSNR) (Kalima, 2006)